Factors associated with recurrent Plasmodium vivax malaria in Porto Velho, Rondônia State, Brazil, 2009 - Luciano Rodrigues Simões; Eduardo Rodrigues Alves Jr; Daniele Ribatski-Silva; Luciano Teixeira Gomes; Andréia Ferreira Nery; Cor Jesus Fernandes Fontes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This open retrospective cohort study aimed to describe the incidence of recurrent Plasmodium vivax malaria and associated factors in Porto Velho, Rondônia State, Brazil, in 2009. Data were collected from the National Information System for Malaria Epidemiological Surveillance. There were 23,365 reported P. vivax malaria cases in 2009, 23% of which were classified as relapses. Incidence density of P. vivax recurrence was 45.1/100 patient-years, mostly occurring between the 4th and 13th week after initiating treatment. Male gender, shorter time since onset of symptoms, and higher parasitemia in the initial infection increased the risk of relapse during the year, with a 10% reduction in relative risk for longer symptoms and 11% and 15% increases in relative risk for males and higher initial parasitemia, respectively. However, the results show low clinical relevance for these associations, thereby limiting their applicability to decision-making at the public health level.